GELIAT USAHA PETERNAKAN SAPI RAKYAT PASCA WABAH PENYAKIT MULUT DAN KUKU DI KABUPATEN KEDIRI - Solikin, Nur; Andaruisworo, Sapta; Yuniati, Erna; Tanjungsari, Ardina; ningrum, Anifiati; Yusuf, M. Ali; Yasin, Hilmy Mahdi (AMMER : JOURNAL OF ACADEMIC & MULTIDICIPLINE RESEARCH; Vol 2 No 03 (2023): EDISI OKTOBER - JANUARIDO - 10.32503/ammer.v2i03.3442, 2023)
Economic impact of livestock and cattle population. The impact of foot and mouth disease (FMD) cannot be avoided. The aim of the study was to analyze the phenomena that occur in smallholder cattle breeders and cattle sellers in the Kediri Regency. Activities start in August – December 2022. Data collection is carried out through interviews, observations, and discussions. Further information was analyzed descriptively qualitatively. The results of the study show that firstly, livestock breeders and traders (cattle) have high anxiety, secondly, cattle breeders and sellers suffer economic and social losses during the FMD outbreak, thirdly the interest or determination to run a livestock business and trade cattle has decreased. It can be concluded from the research that after the FMD outbreak affected the viability of the people's cattle farming business in Kediri Regency. The researcher's advice for cattle breeders and traders remains optimistic in running a business, and following the prevention and control procedures recommended by the government. For related agencies and or the government to continue to motivate and educate breeders intensively, outreach and realization of livestock insurance programs